An analysis of electroacupuncture as adjunctive treatment for insomnia: a new perspective targeting GABA-mediated microbiome-gut-brain axis - Yan, Lijuan; Wang, Xiao; Liu, Xiang; Cai, Jiaying; Zhang, Zuobing; Yang, Bin (Frontiers in Neurology, 2025)
IntroductionInsomnia is a prevalent psychiatric disorder that significantly impacts mental and physical health. Emerging evidence suggests that gut microbiota, particularly γ-aminobutyric acid (GABA) producing bacteria, plays a critical role in the microbiome-gut-brain axis (MGBA), influencing sleep and mental states. Electroacupuncture (EA) has been shown to have favorable anti-insomnia effects. This research protocol outlines a randomized controlled trial (RCT) designed to investigate the efficacy of EA in modulating GABA levels via the MGBA to alleviate insomnia.Methods and analysisThe study will use glutamate (Glu) concentrations of p-chlorophenylalanine (PCPA) -induced insomnia rat model to examine whether EA at specific acupoints can increase GABA levels in the brain and plasma by enhancing the abundance of GABA-producing gut bacteria. A second experiment will transplant stool from insomnia rats into germ-free mice to evaluate the causal role of microbiota in insomnia pathology. Primary outcome measures include changes in GABA and Glu levels, data about the open field test, and gut microbiota composition.DiscussionThis study will provide insights into the therapeutic mechanisms of EA targeting the MGBA in the treatment of insomnia and contribute to the development of novel therapeutic strategies.Ethics and disseminationThis study has been approved by the Laboratory Animal Center of Xiamen University (No. XMULAC20220100). The study findings will be submitted for publication in peer-reviewed academic journals.